Anatomi Daun Beberapa Talas Liar (Colocasia esculenta (L.) Schott dari Kabupaten Bogor - Dorly Dorly; Yohana C Sulistyaningsih (Universitas Sebelas Maret, 2007)
Leaf anatomy characters are commonly stable, however some of them can change because of environmental influence. Identification of those characters are necessary to be conducted by observing anatomical structure of the plants grown out side of the natural habitat. The objective of this research is to examine the stability of leaf anatomy characters of wild taro on their natural habitat and after planted in the dry field. Leaf anatomical observation was conducted by preparing paradermal and transversal sections. The result indicated that leaf anatomical character was the number of palisade layers of Ciju-2 and Jonggol grown out side their natural habitat was stable. Leaf anatomical characters of Ciju-2 collection were palisade thickness, sponge thickness, leaf thickness, stoma density on abaxial surface changed after planted on dry field. Whereas on Jonggol collection significant difference were found on papil height on abaxial surface, stomatal index on abaxial surface, and palisade thickness on dry field and natural habitat.